PREVALENCE OF INTERNET-RELATED ADDICTIVE BEHAVIOR AND ITS SYMPTOMS AMONG ADOLESCENTS BOYS AND GIRLS - Leonova, I. N. (Modern Psychology, 2019)
The paper presents the results of a research of Internet-related addictive behavior and its symptoms in adolescents using the Chen's Internet addiction scale (CIAS). It was found that girls, as compared with boys, more frequently demonstrate the steady pattern of Internet-related addictive behavior, they also demonstrate a higher values of its key symptoms (compulsive, cancellation, tolerance) and problems with time management.
Keywords: Internet addiction, pathological internet use, behavioral addiction, prevalence addiction.